Postmodernisme dalam Film Avatar The Way Of Water - Tegar Buana Harahap; Ratri Rizki Kusumalestari (Bandung Conference Series: Communication Management, 2023)
Abtract. Communication is processed into various forms for the needs of people's lives. Avatar The Way of Water is a phenomenal sci-fi film at the end of 2022 because of the sophisticated technological sophistication and moral values ​​contained in this film. This film tells about the rapid development of technology that can make humans turn into a creature that is more resilient than humans who live on other planets. The purpose of this study is to determine the value of postmodernism contained in the film Avatar The Way of Water through the structure of signs and symbols. The method used in this study is a qualitative method with a semiotic analysis approach. The data collection technique uses image and sound observation or dialogue in which there are sign elements that describe moral values. Then it was analyzed using Roland Barthes' semiotic analysis which analyzed it in two stages, namely the denotation and connotation stages. The results of this study include denotative meanings regarding the existence of families as well as human crimes against nature, then some of the connotative meanings in this film, namely taking care of each other between families under any circumstances, as well as technological advances to support their implementation process. There are two myths in this film, namely regarding family and human consumption of nature. Abtsrak. Semakin pesatnya perkembangan teknologi di era globalisasi ini, perkembangan pesan komunikasi diolah menjadi berbagai bentuk guna kebutuhan kehidupan masyarakat. Avatar The Way of Water merupakan film fiksi ilmiah yang sangat fenomenal pada akhir tahun 2022 karena kecanggihan tekonologi yang mumpuni serta nilai moral yang terkandung pada film ini. Film ini menceritakan tentang perkebangan teknologi yang begitu pesat yang dapat membuat manusia berubah menjadi satu makhluk yang lebih Tangguh dari manusia yang tinggal di planet lain. Tujuan penelitian ini adalah untuk mengetahui nilai posmodernisme yang terkandung dalam film Avatar The Way of Water melalui struktur tanda dan symbol. Metode yang digunakan dalam penelitian ini adalah metode kualitatif dengan pendekatan analisis semiotika. Teknik oengumpulan data menggunakan observasi gambar dan suara atau dialog di dalamnya juga yang terdapat unsur tanda yang menggambarkan nilai moral. Lalu dianalisis menggunakan analisis semiotika Roland Barthes yang menganalisis secara dua tahap, yaitu dengan tahap denotasi dan konotasi. Hasil pada penelitian ini yaitu diantaranya makna denotasi mengenai kebaradaan kelurga juga kejahatan manusia pada alam, lalu beberapa makna konotasi pada film ini yaitu saling menjaga antar keluarga dalam keadaan apapun, juga kemajuan teknologi untuk mendukung proses pelaksanaan meraka. Mitos pada film ini ada dua yaitu mengenai keluaraga dan konsumsi manusia terhadap alam.